2020
DOI: 10.1186/s12871-020-01123-6
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility and efficacy of lung ultrasound to investigate pulmonary complications in patients who developed postoperative Hypoxaemia-a prospective study

Abstract: Background: Postoperative pulmonary complications (PPCs) and hypoxaemia are associated with morbidity and mortality. We aimed to evaluate the feasibility and efficacy of lung ultrasound (LUS) to diagnose PPCs in patients suffering from hypoxaemia after general anaesthesia and compare the results to those of thoracic computed tomography (CT). Methods: Adult patients who received general anaesthesia and suffered from hypoxaemia in the postanaesthesia care unit (PACU) were analysed. Hypoxaemia was defined as an o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…e results showed that patients in the algorithm group were more likely to have decreased lung gas content after operation than those in the control group under the same anesthesia. is result was also consistent with other studies [20][21][22][23][24].…”
supporting
confidence: 93%
“…e results showed that patients in the algorithm group were more likely to have decreased lung gas content after operation than those in the control group under the same anesthesia. is result was also consistent with other studies [20][21][22][23][24].…”
supporting
confidence: 93%
“…Our supine US examination results (sensitivity of 98%, specificity 94.4%, a diagnostic accuracy of 97.1%) are consistent with existing literature. A pooled sensitivity of 93% and specificity of 96% were noted in a prior systematic review [ 16 ], while a diagnostic accuracy of 95.1% was previously reported [ 20 ]. In contrast, for dullness to percussion, our positive LR 1.13 is lower than the previously reported LR of 8.7, although a wide 95% CI (2.2–33.8) was noted [ 5 ].…”
Section: Resultsmentioning
confidence: 95%
“…Lung ultrasound will be facilitated to detect atelectasis, pneumonia, or pulmonary effusion, which are common pulmonary complications. Unfortunately, although some researches are indicating the high sensibility and specificity of LUS to diagnose atelectasis, pneumothorax, and pleural effusion [ 31 , 32 , 43 ], with a diagnostic accuracy of over 90% [ 43 ], there is no consensus on lung ultrasound to diagnose PPCs yet. We, therefore, aim to link the incidence of PPCs to lung ultrasound by analyzing the postoperative ultrasound imaging score and follow-up procedures straight into 30 days after their surgeries.…”
Section: Discussionmentioning
confidence: 99%